Preputial cyst in the newborn: A case report from Africa - Olumide Abiodun Elebute; Muyiwa D Komolafe; A O Akinjo; Felix Makinde Alakaloko; Justina O Seyi-Olajide; Oluwaseun Ladipo-Ajayi; Fatimah Biade Abdulkareem; Adesoji O Ademuyiwa; Christopher O Bode (Wolters Kluwer Medknow Publications, 2023)
Cysts of the prepuce are rare, and documented reports from the English literature are mostly from Asia. Presentations in children are worrisome to the parents. We report a case of a preputial cyst occurring in a neonate who was brought to our facility due to parental anxiety. After a thorough clinical evaluation, a freehand circumcision technique was performed which allowed exposure of the full extent of the cyst, the external urethral meatus and the glans, thus ensuring complete excision and minimising the risk of injury to the adjoining structures. We postulate that preputial cysts are rare in Africa due to the universality of circumcision, which is one of the options of treatment. Preputial cysts are benign foreskin cystic lesions that can be effectively treated with circumcision. This is probably the first reported case of a benign epithelioid preputial cyst from Africa. The paucity of reported cases may be due to the universal practice of circumcision in most of Africa.